In-vitro antimicrobial and antioxidant activities of aqueous pericarp extract of Punica granatum - Eswar Kumar .K, Swathi Putta, Nagendra sastry.Y, DSVGK Kaladhar, Govinda Rao.D. (Journal of Applied Pharmaceutical Science, 2013)
The study aimed to evaluate the anti microbial against human pathogenic organisms and antioxidant activities of aqueous pericarp extract of Punica granatum. The antimicrobial activity was tested against human pathogenic bacteria and fungi. The aqueous pericarp extract of Punica granatum was showed significant inhibitory activity. 11 mm was the highest inhibitory zone against Staphylococcus aureus but not active against C. albicans. The MIC of pericarp extract was found to be the range between 10- 100 µg/ml. 10 µg/ml was the lowest MIC to most of the bacteria. Radical scavenging activity of pericarp extract of P. granutum was carried out to assess antioxidant activity with employing acorbic acid as standard drug. 6.8, 36.3, 4, 65.2, 10.0, 185 µg/ml were the IC50 values of seed coat extract to Superoxide, Hydroxyl, Hydrogen peroxide, DPPH, Nitric oxide, Lipid peroxide radical scavenging activities respectively. The antimicrobial as well as antioxidant activities were dose dependently increased with pericarp extract concentration. The present study revealed that pericarp of Punica granatum has shown significant antimicrobial and antioxidant activities.
Keywords: Punica granutum, Pericarp, Aqueou